Multivariate flood loss estimation in Jakarta - Zhang, Yuwen (2015)
In the past few decades, Jakarta has been threatened by many flood events and suffered tremendous losses. This study was carried out to estimate the economic losses of floods in residential buildings. Through a questionnaire survey and data analysis with MATLAB, a well-fitted linear regression pattern was developed. This pattern revealed the relationship between the affecting factors and the losses and was used for loss estimations. For future studies, it is recommended to use a larger size of samples for better estimation.